2018
DOI: 10.1002/rmb2.12259
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of stromal cell‐derived factor‐1 (SDF‐1/CXCL12) in the follicular fluid is associated with blastocyst development

Abstract: Purpose To study the association between stromal cell‐derived factor‐1 (SDF‐1/CXCL12) and vascular endothelial growth factor (VEGF) concentrations in individual human ovarian follicles and IVF outcomes. Methods Concentrations of SDF‐1 and VEGF in 261 follicular fluid samples were measured with enzyme‐linked immunosorbent assay. IVF outcome parameters were included in fertilization rate, cleavage rate, embryo morphology on day 3, and blastocyst morphology on day 5. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Human leukemia cells cultured in the presence of SDF1 produce low levels of ROS due to lower mitochondrial metabolism [ 24 ]. The level of SDF1 in human [ 25 ] and porcine follicular fluid [ 22 ] is predictive of the outcome of embryonic development. Previous studies have shown that supplementation of SDF1 alone during ovine oocyte IVM can enhance subsequent PA embryo development, and combined supplementation of SDF1 with other factors to porcine oocyte IVM medium can improve subsequent embryo development [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human leukemia cells cultured in the presence of SDF1 produce low levels of ROS due to lower mitochondrial metabolism [ 24 ]. The level of SDF1 in human [ 25 ] and porcine follicular fluid [ 22 ] is predictive of the outcome of embryonic development. Previous studies have shown that supplementation of SDF1 alone during ovine oocyte IVM can enhance subsequent PA embryo development, and combined supplementation of SDF1 with other factors to porcine oocyte IVM medium can improve subsequent embryo development [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…BMSCs have the potential for cross-system and cross-germ differentiation under the action of a specific microenvironment and suitable cytokines/growth factors. They can differentiate into mesodermal and neuroectodermal cells, such as osteoblasts, chondrocytes, endothelial cells, and nerve cells; accordingly, they have recently become a resource for tissue repair [1,2]. Osteogenic differentiation of BMSCs is closely related to bone-related diseases: for example, the inhibition of osteoporosis [3].…”
Section: Introductionmentioning
confidence: 99%